The effect of episodic future thinking ability on subjective cue use when judging credibility - O'Connell, Felicity (Legal and criminological psychology, 2023)
Background Episodic Future Thought (EFT) ability affects how credible individuals appear (O'Connell et al., The effect of individual differences in episodic future thought on the ability to lie about intentions [manuscript submitted for publication], Psychology Department, Lancaster University, 2022). However, it is unclear how individuals with higher EFT ability create this credible demeanour. This paper describes two studies that explored participants' subjective cue use when judging the veracity of verbal statements (Study 1) and written statements (Study 2) provided by individuals with varying EFT ability. Method In Study 1, 68 participants judged the veracity and indicated which cues influenced their veracity judgements of six truthful and six deceptive verbal statements. In Study 2, 102 participants judged the veracity and indicated which cues influenced their veracity judgements of 24 truthful or 24 deceptive written statements. Results Study 1 and Study 2 showed that the EFT ability of the sender affected subjective cue use. In Study 1, participants were influenced by different subjective cues when judging truthful (vs. deceptive) verbal statements. In Study 2, participants reported being influenced by the same cues in both veracity conditions. Study 1 showed that three cues mediated the relationship between EFT ability and veracity judgements. In Study 2, four cues mediated the EFT ability–veracity judgement relationship in the deceptive condition. There were no mediation effects in the truthful condition. Conclusion We propose that EFT ability is an underlying cognitive mechanism involved in creating a credible demeanour which can affect participants' veracity judgements. The current results suggest that the cues present in higher EFT individual's accounts may be contributing to this credibility effect.